Analysis the Effect of Product Quality and Price on Purchase Decision (Case Study of Adidas India, Indonesia, and Malaysia) - Pandey, Rudresh; Reddy, L. Sudershan; Chaudary, Vidush; Widyawati, Venny Tezaryning; Sin, Liem Gai; Bin Mohd Ghazali, Muhammad Khairul Amali; Kee, Daisy Mui Hung; Bin Ibrahim, Muhammad Firdaus; Bin Ahmad Fadzeil, Muhammad Zulhusni; Binti Mohamed, Nur Azwanie (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
Exercising can be an activity to maintain human health. Adidas is a company providing sports equipment and accessories with high quality located in more than 100 countries around the world. This research aims to understand and analyze the effect of product quality and price on the purchase decision of Adidas India, Indonesia, and Malaysia. This research uses a quantitative method, which is Ordinary Least Square (OLS) based on the data collected from the questionnaires with 100 respondents. The results of this research show product quality and price partially affect purchase decision, product quality and price simultaneously or collectively affect purchase decision. The contribution proportion of Adidas product quality and price on the customers' purchase decision is 50.1%.